ANALISIS USAHA ULAT SUTERA SISTEM KEMITRAAN PENGUSAHA DENGAN PETANI ULAT SUTERA DI KECAMATAN LAWANG KABUPATEN MALANG - Paulus, Kristo; Mutiara, Farah; Masduki, Said (Universitas Tribhuwana Tunggadewi, 2019)
The silkworm is a very important product in the production of currencies. At present, the demand for cocoon and silk is increasing, which may offer silkworm producers new opportunities to feed on cassava leaves. The purpose of this study is to determine the partnership system of silkworm entrepreneurs with silkworm breeders and to determine how to analyze the efforts of silkworm breeders in Lawang District. The data analysis method used was descriptive and qualitative to determine the partnership system and analysis of silkworm activities. Data obtained through direct interviews and questionnaires. The partnership model set up by silkworm entrepreneurs with silkworm breeders is a model of partnership based on plasma. Where the contractor is the nucleus that supplies the seeds and sells the silkworms. Farmers in the form of plasma preparing only soils, cages and silkworms. The business analysis in this study includes fixed costs, variable costs, total costs, revenues and profits. The income of each silkworm producer in Lawang Subdistrict is 1,813,250 rupees. According to the results of the study, the role of partnerships in the silkworm sector is very useful and profitable for silkworm farming. It is hoped that researchers will be able to develop research on the partnership of silkworm entrepreneurs. Ulat sutera merupakan komuditas yang cukup penting dalam prolehan devisa negara. Saat ini permintaan kokon dan benang sutera semakin meningkat sehingga dapat memberikan peluang yang prospektif bagi petani ulat sutera dengan pakan daun singkong. Penelitian ini bertujuan untuk mengetahui sistem kemitraan pengusaha ulat sutera dengan petani ulat sutera, dan untuk mengetahui bagaimana analisis usaha petani ulat sutera di Kecamatan Lawang. Metode analisa data yang digunakan secara deskriptif kualitatif untuk mengetahui sistem kemitraan dan analisis usaha ulat sutera. Data diperoleh dengan cara wawancara langsung dan kuisioner. Pola kemitraan yang dilakukan oleh pengusaha ulat sutera dengan petani ulat sutera adalah pola kemitraan inti plasma. Dimana pengusaha sebagai inti yang menyediakan bibit dan menjual ulat sutera. Petani sebagai plasma dimana hanya menyiapkan lahan, kandang, dan pakan ulat sutera. Analisis usaha dalam penelitian ini meliputi biaya tetap, biaya variabel, biaya total, penerimaan, dan keuntungan. Penghasilan setiap petani ulat sutera di Kecamatan Lawang yaitu Rp 1.813.250,-. Dari hasil penelitian, peran kemitraan didalam usaha ulat sutera ini cukup membantu dan menguntungkan untuk dilakukan didalam beternak ulat sutera. Diharapkan peneliti dapat mengembangkan penelitian tentang kemitraan pengusaha ulat sutera.